LGBT in Student Knowledge and Attitudes: Value Education Perspective - Indrawadi, Junaidi; Moeis, Isnarmi; Nurman, Nurman; Luthfi, Zaky Farid (Jurnal Pendidikan Indonesia, 2021)
Lesbian, Gay, Bisexual, and Transgender (LGBT) phenomena are one of the problems of the nation today. These problems become debatable among politicians, legal experts, and academicians. On the other hand, Pancasila Education is a personality development course that transforms the noble values of the nation has not been able to prevent the development of LGBT. Relating to the threats of LGBT, this study aims to develop an anti-LGBT values learning model that is integrated into the Pancasila Education. The initial stage of the study discusses the students’ knowledge and attitudes towards LGBT. A Likert scale questionnaire was employed to collect data; the sample of the study was chosen randomly from students taking the Pancasila Education course. The data were analyzed using SPSS version 20. The research findings indicated that students had sufficient knowledge about LGBT, and they had a firm attitude against LGBT. This finding suggests that most students still have a good practice of religious and traditional values to stay away from LGBT.